STATISTICAL ESTIMATION OF THE LIFE QUALITY OF CENTRAL FEDERAL DISTRICT POPULATION - Vera V. Zholudeva; Nadezhda F. Melnichenko; Georgi E. Kozlov (Статистика и экономика, 2016)
The results of statistical estimation of the life quality of Central Federal Districtpopulation are shown. Methods of clustering and correlation analysis were used.Integral estimation of the life quality wascarried out.